Book Profile: God After Metaphysics: A Theological Aesthetic, by John Manoussakis - Dickinson, Wilson (The journal for cultural and religious theory, 2008)
A book profile of John Panteleimon Manoussakis, God after Metaphysics: A Theological Aesthetic. Indianapolis: Indiana University Press, 2007. xiii + 213 pp. ISBN: 0253348803